Cooperative predation in the social amoebae Dictyostelium discoideum - Rubin, Michelle (PLoS One, 2019)
The eukaryotic amoeba Dictyostelium discoideum is commonly used to study sociality. The amoebae cooperate during development, exhibiting altruism, cheating, and kin-discrimination, but growth while preying on bacteria has been considered asocial. Here we show that Dictyostelium are cooperative predators. Using mutants that grow poorly on Gram-negative bacteria but grow well on Gram-positive bacteria, we show that growth depends on cell-density and on prey type. We also found synergy, by showing that pairwise mixes of different mutants grow well on live Gram-negative bacteria. Moreover, wild-type amoebae produce diffusible factors that facilitate mutant growth and some mutants exploit the wild type in mixed cultures. Finding cooperative predation in D. discoideum should facilitate studies of this fascinating phenomenon, which has not been amenable to genetic analysis before.